Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper focuses on some of the key stylized facts of Korean business and export cycles over 1960-2001, and calculates a chronology for the classical cycle in these series by applying a variant of the Bry and Boschan (1971) cycle-doling algorithm. It highlights that the Korean classical business cycle and exports cycles are extremely asymmetric, as they exhibit long-lived expansions and much shorter-lived contractions. The results also indicate that the probability of ending a contraction or expansion phase in Korean industrial production and Korean real exports is independent of their duration.